2016
DOI: 10.3847/1538-3881/153/1/10
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Proper Motion Catalog Within the Sloan Digital Sky Survey Footprint. Ii. The White Dwarf Luminosity Function

Abstract: , respectively. We resolve the bump in the disk WDLF due to the onset of fully convective envelopes in WDs, and see indications of it in the halo WDLF as well.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 73 publications
3
57
3
Order By: Relevance
“…Hence, the latter survey significantly increases the number of stars beyond the turnover in the disk luminosity function, and it provides an excellent opportunity to disentangle the thin disk and thick disk luminosity functions. Figure 3 presents the disk luminosity function from Munn et al (2017) using the preferred disk model of Jurić et al (2008) with thin and thick disk scale heights of 300 and 900 pc, respectively, and a thick to thin disk ratio of 12%. As in the analysis of the 40 pc luminosity function, we only use stars with M 11 bol > mag in our fits.…”
Section: The Disk Luminosity Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, the latter survey significantly increases the number of stars beyond the turnover in the disk luminosity function, and it provides an excellent opportunity to disentangle the thin disk and thick disk luminosity functions. Figure 3 presents the disk luminosity function from Munn et al (2017) using the preferred disk model of Jurić et al (2008) with thin and thick disk scale heights of 300 and 900 pc, respectively, and a thick to thin disk ratio of 12%. As in the analysis of the 40 pc luminosity function, we only use stars with M 11 bol > mag in our fits.…”
Section: The Disk Luminosity Functionmentioning
confidence: 99%
“…Munn et al (2017) identified 8472 white dwarf candidates in this survey, and used 2839 stars with M 5.5 17 bol = -mag to create a disk white dwarf luminosity function. To avoid contamination from subdwarfs (at the low velocity end), they limited their disk sample to objects with v 40 120 tan = -km s −1 .…”
Section: The Disk Luminosity Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…[38,45] show that photometrically selected white dwarfs have a contamination around 40%. Even the ones selected also from proper motion by [46] show significant contamination by non-white dwarf objects, when spectra are available.…”
Section: Interacting Binariesmentioning
confidence: 99%